Tracing the Evolution and Legacy of Professor A.P. Iofinov’s Scientific School - S. G. Mudarisov; R. R. Kamaletdinov (Сельскохозяйственные машины и технологии)
The scientific ideas and contribution of Professor A.P. Iofinov to the development of agricultural science remain relevant in our time. The paper emphasizes Professor August Pavlovich Iofinov’s pivotal role in the exploration of quality management and the modeling of technological processes for agricultural machines. The scientific concepts introduced by A.P. Iofinov continue to hold significance in contemporary times. Their development and application contribute to improving the operational capabilities of agricultural machinery and bolstering the overall efficiency of the agricultural industry. (Research purpose) The study seeks to consolidate historical and scientific materials about the activities of professor A.P. Iofinov and the creation of a scientific school under his leadership at the Department of Agricultural Machinery of the Bashkir State Agrarian University. (Materials and methods) The establishment and evolution of the scientific school are examined through the problem-chronological method. Scientific issues articulated by Professor A.P. Iofinov, are presented chronological sequence of their progression, moving from hypothesis to practical testing and eventual generalization in scientific works. (Results and discussion) The paper chronicles the founding and progression of the scientific school affiliated with the Department of Agricultural Machines at the Bashkir State Agrarian University, guided by Professor A.P. Iofinov. The established scientific school delved into significant research domains, including the statistical dynamics of agricultural machinery, quality management of agricultural machinery, modeling of technological processes, and yield forecasting. At present, these research areas are experiencing renewed development, with new tasks being formulated to align with contemporary trends and the latest achievements in science and technology. (Conclusions) Professor A.P. Iofinov’s works and his scientific school have given rise to the development of new algorithms and computer programs essential for automating the control processes of agricultural machinery and forecasting yields. Furthermore, they have played a crucial role in the creation of digital twins for agricultural machines, based on models of technological processes. This advancement significantly enhances the precision and efficiency in resource utilization, improves the quality of work, and boosts productivity in agriculture.